Justice Muhammad Ibrahim, 1898-1966 : memorial volume - Ahmed, Sufia; Ibrahim, Muhammad, 1898-1966. (Dhaka : Academic Press and Publishers Library, 2006)
Contributed articles on his life and work.
English and Bengali.
Keywords: Ibrahim, Muhammad, -- 1898-1966.; Judges -- Bangladesh -- Biography